2002
DOI: 10.1038/417515a
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and mechanism of a calcium-gated potassium channel

Abstract: Ion channels exhibit two essential biophysical properties; that is, selective ion conduction, and the ability to gate-open in response to an appropriate stimulus. Two general categories of ion channel gating are defined by the initiating stimulus: ligand binding (neurotransmitter- or second-messenger-gated channels) or membrane voltage (voltage-gated channels). Here we present the structural basis of ligand gating in a K(+) channel that opens in response to intracellular Ca(2+). We have cloned, expressed, anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

56
1,435
2
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,293 publications
(1,497 citation statements)
references
References 39 publications
56
1,435
2
4
Order By: Relevance
“…All four gf mutations in sup-9 cause the same A236T amino acid substitution within the C-terminal half of the fourth transmembrane domain of SUP-9. A comparison of the crystal structures of two bacterial K ir -like channels, the closed KcsA channel (Doyle et al, 1998) and the open MthK channel (Jiang et al, 2002a), suggests that during channel opening, there is a rotation of the transmembrane domains that follow the P-domain (Jiang et al, 2002b). Because the gf substitution occurs within this gating domain, we postulate that the mutant threonine may stabilize the fourth transmembrane domain in its rotated conformation, resulting in a SUP-9 channel that is constitutively open.…”
Section: Discussionmentioning
confidence: 89%
“…All four gf mutations in sup-9 cause the same A236T amino acid substitution within the C-terminal half of the fourth transmembrane domain of SUP-9. A comparison of the crystal structures of two bacterial K ir -like channels, the closed KcsA channel (Doyle et al, 1998) and the open MthK channel (Jiang et al, 2002a), suggests that during channel opening, there is a rotation of the transmembrane domains that follow the P-domain (Jiang et al, 2002b). Because the gf substitution occurs within this gating domain, we postulate that the mutant threonine may stabilize the fourth transmembrane domain in its rotated conformation, resulting in a SUP-9 channel that is constitutively open.…”
Section: Discussionmentioning
confidence: 89%
“…Numbers in parentheses following each channel's name are SWISS-PROT access numbers. of open potassium channels (19) (Figure 5) or the size of tetrabutylammonium or tetrabutylantimony, quaternary amines known to act as open channel blockers by entering into the hydrophobically lined channel inner pore (18). More importantly in regard to this work, the -hairpin proposal explains the results obtained in trying to promote inactivation of the Shaker B∆6-46 K + channel by the ShB-Y8y peptide: D-tyrosine in the peptide chain relocates the bulky phenol ring between the two potential -strands, preventing both hydrogen bonding and the adoption of the -hairpin conformation and thus making the peptide unable to enter the channel inner pore and induce inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…From the above observations, it was concluded that the molecular recognition events leading to the formation of the inactivating peptide/channel complex, and thus to channel inactivation, have a rather unconstrained basis in terms of primary structure and that there must be two relevant domains, complementary to those in the ball peptides, configuring the site for the inactivating peptide in the channel protein: (i) a hydrophobic pocket, which becomes accessible only upon channel opening, separated from the cytoplasm by (ii) a region with a negative surface potential (14)(15)(16). Such conclusions received support from the crystal structure of the prokaryotic KcsA and MthK channels (17)(18)(19) in which the central cavity and inner channel pore are lined by hydrophobic amino acids, while the surrounding cytoplasmic domains contain plenty of acidic amino acids to favor electrostatic interaction with the positively charged amino acids found near the C-terminus in most ball peptides. † Partly supported by grants from the Spanish DGI BFI2002-03410 and BMC2000-0545.…”
mentioning
confidence: 99%
“… a–i , Pairwise superposition of the pore domain in hTRPV6 with ( a ) rat TRPV1 18 (PDB ID: 5IRX; RMSD = 2.065 Å), ( b ) rabbit TRPV2 21 (PDB ID: 5AN8; RMSD = 3.757 Å), ( c ) rat TRPV2 24 (PDB ID: 5HI9; RMSD = 4.399 Å), ( d ) human TRPA1 23 (PDB ID: 3J9P; RMSD = 1.429 Å), ( e ) human PKD2 25 (PDB ID: 5T4D; RMSD = 2.676 Å), ( f ) KcsA from Streptomyces lividans 47 (PDB ID: 1BL8; RMSD = 2.708 Å), ( g ) MthK from M. thermautotrophicum 48 (PDB ID: 1LNQ; RMSD = 2.947 Å), ( h ) rat Shaker 49 (PDB ID: 2A79; RMSD = 2.487 Å) and ( i ) rat GluA2 AMPA-subtype iGluR 28 (PDB ID: 5WEO; RMSD = 2.044 Å). j , Sequence alignment for the pore region of human TRPV3–6, TRPA1 and PKD2, rat TRPV1, 2, 6, Shaker and GluA2, rabbit TRPV2 and bacterial K + channels KcsA and MthK.…”
Section: Extended Datamentioning
confidence: 99%